Rancang Bangun Sistem Informasi Penjualan Tiket Pesawat Dengan Metode Agile Berbasis Web - Hary Saputra; Santi (Journal of Information Systems and Business Technology, 2025)
In the age of digitalization, the public greatly needs ease and speed in the handling of pesawat tiket. As the number of domestic tiket pesawat transactions increases, a system that is efficient, reliable, and secure is required to facilitate these transactions. The purpose of this study is to develop and implement an Agile-based web-based information system for pesawat tiket. The system is built using modern technologies like TypeScript, Next.js, React, Tailwind CSS, Lucia for authentication, Prisma for data management, Ngrok for jarak jauh, and Midtrans for online payment integration. Agile methodology is used to ensure that the development process can be carried out in a flexible and iterative manner in accordance with requirements. This system enables users to make payments securely through Midtrans and to send tiket messages online without having to visit the agent's office.